Bradyarrhythmic Cardiac Arrest—A Rare Manifestation of Fexofenadine Cardiotoxicity. Issue 4 (December 2021) - Ghose, Tapan; Kachru, Ranjan; Dey, Jaideep
A 66-year-old diabetic, hypertensive, and hypothyroid female presented in the emergency department with cardiac arrest, for which cardiopulmonary resuscitation was immediately initiated. She had been on oral fexofenadine for 36 h prior to the event. Post successful resuscitation, her cardiac rhythm showed high-grade atrioventricular block. Patient was treated with mechanical ventilatory support and temporary transvenous pacing. No treatable cause could be identified, and she recovered completely following fexofenadine discontinuation, without need for a permanent pacemaker. She has remained asymptomatic during 1 year of follow-up with no documented arrhythmias. An electrophysiological study at 6 months revealed prolonged HV interval (70 ms) with 1:1 AV conduction and no inducible arrhythmias. This is probably the first reported case of fexofenadine-induced cardiac arrest in a patient without previous history of heart disease.